STANDAR OPERASIONAL PROSEDUR DALAM PELAKSANAAN MENGAMBIL PESANAN TAMU PADA RESTAURANT DI HOLIDAY KARIMUN HOTEL TANJUNG BALAI KARIMUN - Savera Mukti; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the implementation of procedures for taking orders and also to find out the obstacles when taking orders at the Holiday Karimun Hotel Tanjung Balai Karimun restaurant. This study uses descriptive qualitative, with direct observation data collection, interviews and also documentation. The key informants in this study were managers, supervisors, senior waiters and waiters. The results of this study indicate: 1) the implementation of procedures for taking guest orders at the Holiday Karimun Hotel restaurant has been going well and also following the applicable standard operating procedures; 2) provide solutions to deal with obstacles during the implementation of taking orders such as: taking orders manually when situational problems occur, handling guests more calmly, not panicking and being patient with guests, the need for additional waiters if guests come crowded and pay attention to writing neatly at the time of taking orders, the importance of foreign language training such as English from the hotel for waiters so that it is easy to communicate with guests who use foreign languages, during work operations waiters should be professional and not bring personal problems while working. Keywords : Procedure, Taking Order, Food and Beverage Service, Restaurant